Integrasi Nilai Islam dan Teknologi dalam Identifikasi Kebutuhan Pembelajaran - Jelita; Dongoron, Rizkinya; Gusmaneli (INDO PUBLISHING, 2025)
This study aims to analyze the integration of Islamic values and the use of technology in the process of identifying learning needs as a strategic step in developing a relevant and future-oriented curriculum. The background of this study is based on the reality of Islamic education, which often faces a gap between the idealism of religious values and the demands of technological advancement. Through a qualitative approach with literature study and document analysis, this research examines the integrative concept between Islamic educational principles, such as ta'dib and maqashid al-syari'ah, with modern educational technology methods, including data-based needs analysis and digital systems. The results show that the integration of Islamic values in identifying learning needs can strengthen the moral, spiritual, and social orientation of students, while the use of technology enables a more accurate, efficient, and adaptive assessment process. These findings confirm that the synergy between Islamic values and technology is not merely an instrumental approach, but a holistic educational paradigm that places humans as subjects of learning who are moral, intelligent, and competitive in the digital age